IMPLEMENTASI SISTEM INFORMASI PEMERINTAHAN DAERAH (SIPD) DI BPKPAD KABUPATEN KLATEN (STUDI KASUS PADA BAGIAN PERBENDAHARAAN) - Sari, Yesti; Rosmiati, Mia (JURNAL LENTERA BISNIS, 2026)
The implementation of the Regional Government Information System (SIPD) is part of the government’s efforts to achieve integrated, transparent, and accountable regional financial management. BPKPAD of Klaten Regency has started using SIPD to replace SIMDA; therefore, an evaluation of its implementation, especially in the Treasury Division, is necessary. This study aims to analyze the implementation of SIPD using the DeLone and McLean information system success model, which consists of six dimensions: information quality, system quality, service quality, use, user satisfaction, and net benefits. This study employs a qualitative method with data collection techniques through in-depth interviews and observation of employees who use SIPD. The results show that SIPD has helped improve the efficiency and effectiveness of regional financial management at BPKPAD of Klaten Regency. In terms of information quality, SIPD is able to provide sufficiently accurate and relevant data. In terms of system quality, SIPD is considered quite easy to use, although it still experiences technical disruptions at certain times. The service quality of the system manager is considered quite good, although handling disruptions still requires time. SIPD has become part of daily work activities, and in general, users are quite satisfied. In addition, SIPD also provides benefits in increasing transparency and accountability, as well as supporting decision-making in regional financial management.